Race and stroke mortality in Brazil - Lotufo, Paulo Andrade (Faculdade de Saúde Pública da Universidade de São Paulo, 2013)
As stroke mortality rates according to race were not known in Brazil, data on mortality for the year 2010 was collected from the Mortality Information System of the Brazilian Ministry of Health. Cerebrovascular mortality rates adjusted for age (per 100,000) were calculated with a confidence interval of 95% (95%CI) by sex and race/skin color. The differences between races were significant for men with rates of 44.4 (43.5;45.3), 48.2 (47.1;49.3) and 63.3 (60.6;66.6) for white, brown and black, respectively; and for women, with rates of 29.0 (28.3;29.7), 33.7 (32.8;34.6) and 51.0 (48.6;53.4) for white, brown and black, respectively. The burden of stroke mortality is higher among blacks compared to brown and white.